Influence of the technology of aluminum waste melting on the composition and the possibility of using the generated dust - L. V. Tribushevskiy; B. M. Nemenenok; G. A. Rumiantseva (Литьë и металлургия, 2018)
It is shown that the amount of flux used in melting significantly influences the composition and volume of dust and gas emissions. Based on the results of the chemical analysis of dust a solution was adopted for the fluxless melting of aluminum waste. In this case, the proportion of chlorine-containing compounds is 1.4% at 75% of aluminum oxides, which makes it possible to use the formed dust to produce a deoxidizing mixture or a refiner slag. On the basis of balance melting, it is shown that with fluxless melting of aluminum waste, a waste-free processing technology is realized, ensuring ecological and economic effects.